Pengaruh Overclocking Processor AMD Ryzen 5 Pada Rendering Video Menggunakan Adobe After Effect - Andika Agus Slameto (P3M Politeknik Negeri Bengkalis, 2020)
Abstract - Video projects in Adobe After Effect usually use a very large number of effects, so this can increase the duration of video rendering. One of the main components of a computer that is responsible for the performance of a computer when rendering is the processor. Efforts to improve processor performance can be done using the overclocking method. Overclocking can be done over UEFI or using the on-the-fly method on Windows 10 using AMD Ryzen Master application. Overclocking on the processor allows the processor to run faster than the default conditions. In this study, the author uses an AMD Ryzen 5 2400G processor. After overclocking the processor, stability testing will be performed using the Cinebench R20 five times in a row. After the video rendering is tested using Adobe After Effect and the results obtained in the form of the length of time required for rendering a video. The time needed for rendering the video is used as a reference for the author to find out how much increased performance after overclocking.